Resisting self-stigma and re-defining obsessive-compulsive disorder in Hanna Alkaf’s the weight of our sky: a psychoanalytic study - Anildeep, Baljit Singh Gill (2021)

(untitled)
The stigma of OCD is getting prevalent day by day because of the misconceptions from the public. Thus, this causes a person with OCD to internalize these stigmatizing beliefs which causes self-stigma. Therefore, this study aims to explore OCD and to counter self-stigma by using concepts from the psychoanalytic theory in Hanna Alkaf’s The Weight of Our Sky. This study addresses the personality of the protagonist, Melati that explores her OCD by using the Id, Ego and Superego followed by the defense mechanisms to overcome her OCD. In addition, this study also addresses the evaluation of the protagonist’s ego strength to counter the selfstigma of her mental illness. Based on the findings, the Djinn which is arguably the superego of the protagonist is the most dominant and punitive personality element that causes her OCD because it is not in harmony with the id and ego. This study also found out that she makes the effort to use more adaptive defense mechanisms compared to maladaptive ones. The analysis argues that certain defense mechanisms that are maladaptive could be adaptive and vice versa such as wishful thinking and suppression. Besides, the analysis suggests that she shows a form of resilience in countering self-stigma upon evaluating her ego strength. Implications of this study suggest that readers would be able to use a psychoanalytical approach to understand OCD as well as to overcome self-stigma through understanding a person’s personality.